2009 IEEE/LEOS Winter Topicals Meeting Series 2009
DOI: 10.1109/leoswt.2009.4771759
|View full text |Cite
|
Sign up to set email alerts
|

Widely-tunable triply-resonant optical parametric ring oscillator

Abstract: We present a widely-tunable low-threshold all-fiber optical parametric ring oscillator that is resonant for the pump wavelength and the two sidebands. For some detunings, threshold can be achieved with as little as 0.7W peak power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The oscillation is similar to modulation instability lasing [6][7][8][9] and parametric oscillation in optical fibers [10][11][12][13][14]. The nonlinear process can be described using externally driven damped nonlinear Schrödinger equation (NLSE) with periodical boundary conditions [15] and, hence, is closely related to the nonlinear phenomena observed in a variety of physical systems [16][17][18][19], including dipolar excitations in one-dimensional condensates [20], optical soliton propagation in a dispersive ring cavity in the presence of an input forcing beam [21], a long Josephson junction in a periodic field [22], easy-axis ferromagnets in a rotating magnetic field perpendicular to the easy axis [23,24], and plasmas driven with radio-frequency radiation [26].…”
Section: Introductionmentioning
confidence: 64%
“…The oscillation is similar to modulation instability lasing [6][7][8][9] and parametric oscillation in optical fibers [10][11][12][13][14]. The nonlinear process can be described using externally driven damped nonlinear Schrödinger equation (NLSE) with periodical boundary conditions [15] and, hence, is closely related to the nonlinear phenomena observed in a variety of physical systems [16][17][18][19], including dipolar excitations in one-dimensional condensates [20], optical soliton propagation in a dispersive ring cavity in the presence of an input forcing beam [21], a long Josephson junction in a periodic field [22], easy-axis ferromagnets in a rotating magnetic field perpendicular to the easy axis [23,24], and plasmas driven with radio-frequency radiation [26].…”
Section: Introductionmentioning
confidence: 64%
“…The oscillations occurring in coherently driven passive optical fiber resonators were studied from the perspective of temporal cavity solitons [62,63], belonging to a general class of dissipative solitons [64], modulation instability lasers [65][66][67][68][69] as well as parametric oscillators [70][71][72][73][74].…”
Section: Resonant Oscillationmentioning
confidence: 99%
“…Many of other studies were interested in the cavity design in order to achieve doubly resonant OPOs, very interesting for there lower threshold particularly for continuous wave operation [12][13][14]. Triply resonant OPOs are also achieved, in which the pump, the signal, and the idler are simultaneously resonant [15][16][17]. The PPLN demonstrated that it is the ideal crystal to generate in the mid-infrared range (2-4) μm above 1 μJ energy per pulse.…”
mentioning
confidence: 99%